2002
DOI: 10.1046/j.1365-2656.2002.00631.x
|View full text |Cite
|
Sign up to set email alerts
|

Density‐dependent growth in brown trout: effects of introducing wild and hatchery fish

Abstract: Summary 1.Although it is not clear to what extent density dependence acts on the survival, emigration or growth of organisms, experiments testing alternative explanations are rare. A field experiment on 1-year-old brown trout (Salmo trutta L.) was undertaken to address the following questions: are the mortality, movement and growth of wild stream-living trout affected by population density? If so, are the density-dependent effects of released hatchery trout different from the effects of wild fish? 2. In each o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
147
2
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(182 citation statements)
references
References 38 publications
32
147
2
1
Order By: Relevance
“…In contrast, brown trout relative abundance, grassland and cultivated riparian area, and thermal sensitivity had minor or nonexistent effects on growth. This supports conclusions reached by Dieterman et al (2012), who noted that limestone bedrock geology and agricultural watersheds promote high productivity in southeast Minnesota streams such that typical brown trout growth factors like prey availability, intraspecific density, social dominance are less important than in other regions (Bohlin et al 2002;Kaspersson & Hojeso 2009). Although thermal sensitivity did not explain spatial variation in an annual index of growth (MBLAA), previous research indicated late-winter brown trout condition (relative weight; Neumann et al 2013) was positively associated with groundwater input and negatively associated with thermal sensitivity in southeast Minnesota streams (French 2014;French et al 2014).…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, brown trout relative abundance, grassland and cultivated riparian area, and thermal sensitivity had minor or nonexistent effects on growth. This supports conclusions reached by Dieterman et al (2012), who noted that limestone bedrock geology and agricultural watersheds promote high productivity in southeast Minnesota streams such that typical brown trout growth factors like prey availability, intraspecific density, social dominance are less important than in other regions (Bohlin et al 2002;Kaspersson & Hojeso 2009). Although thermal sensitivity did not explain spatial variation in an annual index of growth (MBLAA), previous research indicated late-winter brown trout condition (relative weight; Neumann et al 2013) was positively associated with groundwater input and negatively associated with thermal sensitivity in southeast Minnesota streams (French 2014;French et al 2014).…”
Section: Discussionsupporting
confidence: 85%
“…Group members were defined as familiar neighbouringterritory holders. Fishes from different sites (more than 100 m apart) were defined as unfamiliar with one another because trout very rarely move more than 100 m (Bohlin et al 2002). Groups of captured trout were transported back to the laboratory in separate containers of water.…”
Section: Methodsmentioning
confidence: 99%
“…The observed populations in the main river basins (Vydra and Křemelná Rivers) are essentially dependent on spawning migrants from downstream areas of the Otava River. Therefore, it can be suggested that wise management of hatchery fish stocking and the fisheries themselves [49,50] and the restoration of longitudinal river continuity [51] in downstream river stretches are necessary to achieve viability of the brown trout populations in Šumava National Park.…”
Section: Discussionmentioning
confidence: 99%